2016
DOI: 10.1101/092437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NeuroGFX: a graphical functional explorer for fruit fly brain circuits

Abstract: Recently, multiple focused efforts have resulted in substantial increase in the availability of connectome data in the fruit fly brain. Elucidating neural circuit function from such structural data calls for a scalable computational modeling methodology. We propose such a methodology that includes i) a brain emulation engine, with an architecture that can tackle the complexity of whole brain modeling, ii) a database that supports tight integration of biological and modeling data along with support for domain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Note that LNs are connecting pre-/post-synaptically to the OSN-to-PN synapses in each glomerulus. While additional LN types both in terms of innervation patterns and neurotransmitter profile exist [12,31,32,34], we found that these three LN types, and the uni-glomerular PNs (henceforth referred to simply as PNs) alone, are sufficient for disentangling the syntactic and semantic information streams of the odorant stimuli. The functional significance of other LN/PN types remains an open question.…”
Section: Introductionmentioning
confidence: 69%
“…Note that LNs are connecting pre-/post-synaptically to the OSN-to-PN synapses in each glomerulus. While additional LN types both in terms of innervation patterns and neurotransmitter profile exist [12,31,32,34], we found that these three LN types, and the uni-glomerular PNs (henceforth referred to simply as PNs) alone, are sufficient for disentangling the syntactic and semantic information streams of the odorant stimuli. The functional significance of other LN/PN types remains an open question.…”
Section: Introductionmentioning
confidence: 69%
“…NeuroGFX provides a reconfigurable graphical interface for navigation, manipulation, and execution of the CX neural circuit; a screenshot of this interface appears in Figure 3 . (Yeh et al, 2016 ). Regions of neuropils comprised by and accessory to the central complex may be rendered in 3D.…”
Section: Software Architecturementioning
confidence: 99%
“…(Yeh et al, 2016). Regions of neuropils comprised by and accessory to the central complex may be rendered in 3D.…”
Section: Software Architecturementioning
confidence: 99%